Knowledge about diabetes in Malmö prior to initiation of “Cities Changing Diabetes” - Annersten Gershater, Magdalena; Rämgård, Margareta; Holmberg, Cecilia Nagorny; Grahn, Mathias; Zdravkovic, Slobodan (Frontiers in Public Health, 2025)
AimTo identify existing public knowledge regarding diabetes and diabetes-related services offered to persons living with diabetes in the City of Malmö.MethodsA literature review of City of Malmö’s website, public statistics, School health documentation, job databases, education programs, local newspaper, Swedish National Diabetes Register, and PubMed was performed in 2020.ResultsWe identified political decisions about diabetes nurses in home care, financing a project about diabetes complications, and funding support in schools for designated children. Schools had no registrations of diagnoses. Diabetes was common among pregnant women. The local newspaper discussed children and older people with diabetes asking for increased support. Job listings did not require diabetes-relevant competencies. Curricula for nursing assistants did not mention diabetes. National Diabetes Register reported 16,658 persons in Malmö. Three articles were identified in PubMed.ConclusionPublic documents in Malmö did not mention diabetes despite being responsible for caring for persons with diabetes.